The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1159/000487400
|View full text |Cite
|
Sign up to set email alerts
|

Punicalagin and (–)-Epigallocatechin-3-Gallate Rescue Cell Viability and Attenuate Inflammatory Responses of Human Epidermal Keratinocytes Exposed to Airborne Particulate Matter PM10

Abstract: Background/Aims: Airborne particulate matter with a diameter of < 10 µm (PM10) causes oxidative damage, inflammation, and premature skin aging. In this study, we evaluated whether polyphenolic antioxidants attenuate the inflammatory responses of PM10-exposed keratinocytes. Methods: Primary human epidermal keratinocytes were exposed in vitro to PM10 in the absence or presence of punicalagin and (–)-epigallocatechin-3-gallate (EGCG), which are the major polyphenolic antioxidants found in pomegranate and green te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 29 publications
(32 reference statements)
3
44
0
Order By: Relevance
“…The WHO has set daily exposure limits for PM2.5 and PM10 of 25 and 50 mg/m 3 , respectively. 38) Namely, the UPM concentration of 10 µg/mL used in our experiment is not high, compared with the daily exposure limits for particulate matter. When the EMT process having the loss of adherent phenotype is progressed, cell invasion occurs along with the secretion of MMPs.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The WHO has set daily exposure limits for PM2.5 and PM10 of 25 and 50 mg/m 3 , respectively. 38) Namely, the UPM concentration of 10 µg/mL used in our experiment is not high, compared with the daily exposure limits for particulate matter. When the EMT process having the loss of adherent phenotype is progressed, cell invasion occurs along with the secretion of MMPs.…”
Section: Discussionmentioning
confidence: 76%
“…When the EMT process having the loss of adherent phenotype is progressed, cell invasion occurs along with the secretion of MMPs. 39) Because the high mortality of lung cancer is closely associated with its early metastasis, 26) we investigated whether 0.5 µM of CA attenuates the human alveolar cells invasion. Our results provided further evidence that protective effect of CA on UPM-induced the invasion which is typical characteristics of tumor development.…”
Section: Discussionmentioning
confidence: 99%
“…3a) was the most abundant catechin in GTE and is commonly used in cosmetics, functional foods, and dietary supplements due to its health bene ts [54,55]. EGCG has also been shown to reduce FDP-induced skin in ammation in epidermal keratinocytes and dermal broblasts [26,28]. Myricetin (Fig.…”
Section: Combined Effects Of the Green Tea Components On Fdpinduced Cmentioning
confidence: 99%
“…Similar to N-acetyl cysteine [25], EGCG exhibits scavenging e cacy against FDP-induced ROS [26]. EGCG also reduces skin in ammation and asthma in rats caused by FDP stimulation [26,27,28]. However, the studies that have revealed these ndings have concentrated only on active EGCG.…”
Section: Introductionmentioning
confidence: 99%
“…However, oral supplements containing green tea were ineffective in protecting skin from UVR damage [188]. Studies with human keratinocytes treated with airborne pollutants (PM10), showed that EGCG blocked the pollutant induced increase in NADH oxidases, IL-1, TNF-alpha, IL-8, and MMP-1 [202]. In other studies, EGCG reduced the UVR-induced increase in COX-2 in human keratinocytes, but had the opposite effect on human fibroblast cultures, where it increased the expression of both COX-2 and MMP-1 [203].…”
mentioning
confidence: 99%